Penyembuhan Ilahi sebagai Epistem Pedagogis: Rekonstruksi Pendidikan Kristiani-Pentakostal melalui Pendekatan Spirit-led learning - Putri, Ayu Purnama; Siahaan, Harls Evan; Khandira, Michael Erfian (STT Iman Jakarta, 2025)
Contemporary Christian education faces epistemological challenges in integrating the pneumatological dimension into academic learning constructs shaped by the secularist paradigm. This study develops a theoretical framework for Pentecostal Christian education that integrates divine healing as a pedagogical epistemology through the Spirit-led learning model. Using an interpretive qualitative approach, this research integrates theological, phenomenological, and pedagogical analysis through bibliographic studies and analysis of healing experiences in the Pentecostal tradition. Findings show that divine healing has a holistic pedagogical dimension that is experiential, embodied, and communal, teaching faith that is not only conceptual but transformative. Spirit-led learning is synthesized from the convergence of Mezirow and Freire's transformational learning theory with Pentecostal pneumatology, placing the Holy Spirit as Magister Supremus in the pedagogical process. This model actualizes multidimensional transformation—cognitive, affective, and spiritual—while shifting the orientation of education from the transmission of knowledge to existential formation. The research produced pedagogical guidelines for implementation in formal and nonformal educational contexts that facilitate learners' holistic transformation. Pendidikan Kristen kontemporer menghadapi problematika epistemologis dalam menginte-grasikan dimensi pneumatologis dengan konstruksi pembelajaran akademik yang didominasi paradigma sekularisme. Penelitian ini mengembangkan kerangka teoretis pendidikan Kristen Pentakosta yang mengintegrasikan penyembuhan ilahi sebagai epistemologi pedagogis melalui model Spi-rit-led learning. Menggunakan pendekatan kualitatif interpretatif, riset ini mengintegrasikan analisis teologis, fe-nomenologis, dan pedagogis melalui kajian bibliografis serta analisis pengalaman penyembuhan dalam tradisi Pentakostal. Temuan menunjukkan bahwa penyembuhan Ilahi memiliki dimensi pedagogis holistik yang bersifat experiential, embodied, dan komunal, mengajarkan iman yang tidak hanya konseptual tetapi transformatif. Spirit-led learning disintesiskan dari konvergensi teori pembelajaran transformasio-nal Mezirow-Freire dengan pneumatologi Pentakostal, menempatkan Roh Kudus sebagai Magister Supremus dalam proses pedagogis. Model ini meng-aktualisasikan transformasi multidimensional—kog-nitif, afektif, dan spiritual—sekaligus meng-geser orientasi pendidikan dari transmisi pengetahuan menuju formasi eksistensial. Penelitian menghasilkan guidelines pedagogis untuk implementasi dalam konteks pendidikan formal dan nonformal yang memfasilitasi transformasi holistik peserta didik.